APOLOGY AND COMPENSATION STRATEGY ON CUSTOMER FORGIVENESS AND NEGATIVE WORD OF MOUTH - Resekiani Mas Bakar; Nurul Hidayati; Inastuti Retno Giffani (Jurnal Manajemen dan Kewirausahaan, 2019)
The service provider could not totally guarantee the service process without any failure at all. This study aims to measure the influence of service recovery strategy towards customer forgiveness and negative word-of-mouth (WOM) as the effect of service failure. The service recovery strategy is performed in three types of vignette: apology, compensation, and apology-compensation. Vignette was given to 94 participants who have encountered service of airline. The result of ANOVA shows that apology compensation achieves the highest score relates to forgiveness. The interesting result of this study shows that even the customers forgive the service provider due to the service failure they did, this cannot diminish the intention of negative WOM. This study offers an implication to the company in order to pay attention regarding the compensation and the spread of negative WOM to the other customers